Proposição de uma tecnologia cuidativo-educacional sobre sífilis gestacional e congênita com foco na gestante e no parceiro - (:unkn) unknown (UNIFAP - Universidade Federal do Amapá, 2023)
Objective: to gather relevant information for proposing a care-educational technology on gestational syphilis and congenital syphilis to support health education with pregnant women and their partners. Method: methodological research based on context-based production construction, divided into two stages, the first consisted of carrying out an integrative review and the second, in semi-structured interviews with a group of 8 pregnant women and 6 partners to analyze the knowledge of the public- target, the interviews were analyzed using Bardin's categorical analysis. Results: both the review and the interviews exposed the difficulty of understanding about gestational syphilis and congenital syphilis, from forms of transmission, exams, diagnosis, prevention, treatment, maternal-fetal complications; the low perception of vulnerability; difficulty in understanding what was passed on about the theme in prenatal consultations; the partner's low adherence to prenatal care and their non participation in the treatment. Final considerations: it is pointed out that the possibility of creating a care-educational technology aimed at this public could be beneficial as it would encourage the empowerment of pregnant women about care in the context of syphilis, in addition to being created to be shared mainly with partners.
Keywords: Educação em Saúde; Gestantes - Cuidado Pré-Natal; Educação em Saúde; Infecções Sexualmente Transmissíveis (ISTs); CNPQ::CIENCIAS DA SAUDE::ENFERMAGEM::ENFERMAGEM DE SAUDE COLETIVA; ODS 3 – Saúde e bem-estar; ODS 4 – Educação de qualidade; ODS 5 – Igualdade de gênero